2016
DOI: 10.1080/09649069.2016.1239346
|View full text |Cite
|
Sign up to set email alerts
|

‘Letters aren’t good’: the operation of the right to request flexible working post-maternity leave in UK small and medium-sized companies

Abstract: This article contributes to existing literature on flexible working at an organisational level by presenting the results of a qualitative study of women employees and managers in small firms who have been involved in negotiating part-time hours on return to work post-maternity leave. The study finds that the right to request flexible working has become embedded in the policies of small firms and that the overwhelming experience of women employees was positive: their requests were accepted because they were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Studies discussing the impacts of utilization of FFPs on various aspects of women's careers were included (Masood and Nisar, 2020;Shanmugam and Agarwal, 2019;Wheatley, 2017;Formankova and K riz ˇkova, 2015) Studies explaining the difficulties faced in availing or implementation of FFPs were excluded (Chung, 2019;Atkinson, 2016;Munsch, 2016;Gatrell et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies discussing the impacts of utilization of FFPs on various aspects of women's careers were included (Masood and Nisar, 2020;Shanmugam and Agarwal, 2019;Wheatley, 2017;Formankova and K riz ˇkova, 2015) Studies explaining the difficulties faced in availing or implementation of FFPs were excluded (Chung, 2019;Atkinson, 2016;Munsch, 2016;Gatrell et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…In this step, 181 articles were removed and 95 articles were retained for further review. Thereafter, each of these remaining articles were studied in detail and following criteria were set to further include or exclude a study: Studies discussing the impacts of utilization of FFPs on various aspects of women’s careers were included (Masood and Nisar, 2020; Shanmugam and Agarwal, 2019; Wheatley, 2017; Formankova and Křižkova, 2015) Studies explaining the difficulties faced in availing or implementation of FFPs were excluded (Chung, 2019; Atkinson, 2016; Munsch, 2016; Gatrell et al , 2014). Studies which explained about the adverse impacts of FFP usage only on males’ careers were excluded (Noback et al , 2016; Vandello et al , 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, workplace culture and support and its impact on parenthood and maternity leave may be critical contributing factors to mothers’ QML. For example, a generally supportive workplace culture may include supervisors informing mothers of organizational policies regarding leave, benefits, and breastfeeding; offering flexible work schedules or location (e.g., telecommuting); and providing support to employees in utilizing these policies (Atkinson, 2016; Boushey, 2008; Cabrera, 2009; Goodman, 2018). In contrast, some workplace cultures may be unsupportive of caregiving roles, unwilling to provide flexibility, and unhelpful in providing adequate information regarding benefits available to employees.…”
Section: Methodsmentioning
confidence: 99%
“…51,52 Flexible work schedule policies were initiated to address childcare responsibilities and gave employees the right to request changes in when they work (flextime), how many hours they work (flexload), and where they work (flexplace). 53 Employers are obligated to formally respond to these requests, indicating whether the changes can be accommodated and the specific grounds for any refusals, such as cost or customer demands. 54 Multiple studies involving small, medium, and large employers have shown that such policies enhance employees' desire to work at companies that offer them.…”
Section: Legal Right To Request Flexible Reasonable Work Schedulesmentioning
confidence: 99%